A micro-rheological and rheological study of biopolymers solutions: Hyaluronic acid. (1st January 2019) - Dodero, Andrea; Williams, Rhodri; Gagliardi, Simona; Vicini, Silvia; Alloisio, Marina; Castellano, Maila
Highlights: Hyaluronic acid used as injectable fillers containing nanoparticles or biomolecules. Combination of Dynamic Light Scattering and traditional rotational rheometry. Hydrodynamic radius and conformation of a polyelectrolyte in a saline environment. Accessible frequency range significantly extended. Parameters of the network created by the chain entanglements. Abstract: Hyaluronic acid (HA) solutions represent an important class of biomedical products, mostly used as viscosupplements in orthopaedics and as fillers in the cosmetic industry. The focus of the present work is the hydrodynamic, micro-rheological and rheological characterization of HA in physiological saline. Standard viscoelastic characterization techniques were coupled with micro-rheological measurements, i.e. by measuring the passive motions of particles embedded in the samples via Dynamic Light Scattering (DLS), effectively extending the accessible frequency range typical of standard rheometers. The influence of molecular weight and polymer concentration on the storage modulus (G'), loss modulus (G") and complex viscosity (η*) of HA saline solutions was investigated. A brief comparison with theoretical models was made showing such concentrated solutions to be of a semi-flexible nature. In addition, the entanglement concentration ν, the critical molecular weight M ¯ c, and the mesh size ξ of the physical network created by the entangled polymer chains were calculated.